LEVEL OF SCIENCTIFIC LITERACY ABILITY OF MIDDLE SCHOOL STUDENTS IN MEDAN BASED ON FRAMEWORK PISA 2018 - Aristo Hardinata; Mariati P Simanjuntak; Ely Djulia; Sunita K Purba; Koriatul J Siregar; Ghania D U Lubis (UNIVERSITAS NEGERI MEDAN, 2023)
Based on the PISA 2022 results, the scientific literacy abilities of Indonesian students are still below the international average. This research aims to see the level of scientific literacy abilities of junior high school students in Medan City in 2023. This research was carried out at several representative schools designated by researchers as schools representing sub-districts in Medan City. Sample selection was carried out using stratified random sampling. From the 21 sub-districts in the city of Medan, one superior junior high school in each sub-district was selected. From the 21 selected schools, 1 superior 8th grader from that school was taken from each school. The instruments used are scientific literacy questions which have previously been developed by researchers following the indicators set out in the PISA 2018 framework which consists of 15 indicators for 3 scientific literacy competencies in the PISA 2018 framework. It can be concluded that the average scientific literacy ability of students in Medan City was still in the sufficient category. Student achievement was still low in several PISA 2018 framework scientific literacy competency indicators